A thousand and one [videorecording (DVD)] - Rockwell, A. V.; Taylor, Teyana, 1990-; Catlett, William; Abney, Terri; Reynolds, Delissa (Focus Features, 2023)
Follows unapologetic and free-spirited Inez, who kidnaps her six-year-old son, Terry, from the foster care system. Holding onto their secret and each other, mother and son set out to reclaim their sense of home, identity, and stability in a rapidly changing New York City.